(untitled) (Journal of history, 2019)
In the new conditions of the formed independence, the theoretical and methodological approaches to the study and analysis of our past have not only expanded, but also enriched. The significance of the theoretical foundations and methodological approaches in understanding and interpreting historical processes has increased. In other words, the importance of developing the theoretical foundations of historical knowledge and using new methods has increased. The collapse of the communist party, which had an ideological influence on historical science, failed to overcome the challenge of time and the independent development of the republic opened up the possibility of a comprehensive study of the consequences of totalitarian rule in Kazakhstan. Formulating problems in a new way requires a search for a wide range of sources and their introduction into scientific circulation. As clearly stated in the article «Seven Facets of the Great Steppe» by Elbasy, it is necessary to conduct fundamental research of all domestic and foreign archives, covering information from ancient times to modern times. Based on this, the principles of working with documents, their classification and the problem of analyzing information as a source become relevant. In this regard, the author in the article analyzes the documents of the Kirghiz Regional Party Committee, based on the principles of scientific classification and types of archival documents. The features and the source value of party documents are considered on the basis of specific, group and other classifications.